"الفتنہ " کا فقہی و معنوی اطلاق تفسیر قرطبی کی روشنی میں : The jurisprudential and semantic application of "Al-Futna" in the light of Tafsir al-Qurtubi - Dr Javaria Hassan; Huma Bukhari (International Research Journal of Arabic and Islamic Studies, 2024)
Fitna is a small word to say, but it is very deep in terms of effects. In the Holy Quran, the meaning of fitna has been used in many meanings. Recognizing the meanings is also a big test. One of the most important discussions in the Holy Qur'an is the discussion of sedition, the meaning of which is to know about its philosophy and to gain knowledge and to know how to succeed in this sedition is no less than a blessing for a human being. The effects of temptation on man are also for the training of man, because temptation is a Divine Sunnah and is a general thing, that is, it includes all human beings and has a special effect on human happiness, doubt and punishment. Generally, "Al-Fitna" is applied in the sense of test and trial. But it is not necessary that this test is only in evil, rather Allah tests a person in both evil and good, to what extent a person keeps his self under control and walks on the right path. In the Holy Qur'an, the word "fitnah" has been applied in many meanings, the commentators have explained these meanings in their interpretations. So that all people will be aware of the temptation of Khairushar. In this paper, Abu Abdullah Muhammad bin Ahmad in his Tafsir al-Qurtubi, what is meant by the word Al-Fitna will be researched.